Jamaica : Weather Insurance for the Coffee Sector Feasibility Study - World Bank (Washington, DC, 2013)
The present report is intended as a technical, organizational and financial summary of the feasibility study to review options and to make decisions on whether or not this program meets the needs of the industry. It is recognized that decisions on whether or not to proceed towards a future insurance program will require significant consultation with farmers and processors, and an agreement on an implementation plan, including decisions on pilot testing. Chapter two describes the risk modeling undertaken during the study and the outputs. These outputs are used to define key elements of a parametric insurance product, such as zoning of coffee farmers within the blue mountain area, the frequency and severity of the wind hazard, and how the expected impact of those hazards was estimated by division into altitude bands to create vulnerability profiles. Finally the outputs can be used to price different insurance options. Chapter three considers the organizational options and requirements to deliver a parametric insurance product to coffee farmers, and some financial implications including structuring insurance and reinsurance protection. Chapter four considers the issues and steps which will be needed for implementation, including options for piloting and scaling up, and legal and regulatory requirements.